The physiological and perceptual effects of plant extracts (Catha Edulis Forsk) during sustained exercise. Issue 1 (December 2016) - Sallam, Mowaffaq; Sheikh, Kamaludin; Baxendale, Ronald; Azam, Mohammad; El-Setouhy, Maged
Abstract Background Khat (Catha Edulis Forsk) is a natural psychoactive substance that contains addictive substances such as Cathine and Cathinone which have similar structure and action to amphetamine. This substance has been suggested that it can decrease perceived exertion and thus improve performance. There is no study in the literature regarding the effect of khat on exercise performance. Therefore, the aim of this study is to find out whether khat leaves can decrease perceived exertion in humans. Methods This study is an experimental crossover study conducted at the Substance Abuse Research Centre in Jazan University, Saudi Arabia. Twenty one healthy volunteers were randomly assigned into two experiment trials. Each volunteer visited the lab three times. The first visit was a familiarization session about the nature of the study and the equipment. On the second visit, 45 min before the experiment volunteers ingested either 33 ml of fruit juice (placebo) or the juice mixed with 45 g of ground khat leaves. Then the participants were instructed to perform a 10 Km cycling on an ergometer and recorded the following physiological variables repeatedly on every 5 min of cycling: heart rate, time to complete 10 km cycling, tympanic temperature, and perceived exertion rate. On the third visit a crossover trial was conducted one week after the second visit; then the same cycling test was performed and the same variables were recorded as the second visit. The experimental protocol was reviewed and approved by Research Ethical Committee of the Medical Research Centre, Jazan University. Results According to study results, khat dramatically decreased time taken to complete a 10 km cycling time trail (p  < 0.05), and significantly increased heart rate (p  < 0.05) and tympanic temperature (p  < 0.01). However, khat did not reduce participant's perceived exertion during the physical trial. The Bonferrini simultaneous confidence intervals using multivariate Hotelling's T2 was performed to test the significance of the mean vectors for the placebo group and the Khat group and found that groups are statistically significant. Conclusions Khat showed a clear enhancing effect on physical performance. The most parsimonious explanation for this effect is that, like the related amphetamines, cathine/cathinone act as stimulants to increase the capacity to perform exercise. Thus, khat produces the same effects which lead to the banning of amphetamine. These findings conform & endorse the recent prohibition of cathinone by the World Anti-Doping Agency (WADA, 2014).